ANALISIS KONTEN PENDIDIKAN SEKSUALITAS BAGI PARA REMAJA PADA AKUN INSTAGRAM @TABU.ID - Aulia Khairani; Muhammad Husni Ritonga; Faisal Riza (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to find out how the contents of sexuality education for youth on @tabu.id’s instagram based on seven components Comprehensive Sexuality Education by International Planned Parenthood Association. The theory used in this study is the theory of media ecology. This study uses a qualitative content analysis method. Data collection techniques are carried out in the form of observation techniques, documentation and categorization. The data analysis technique in this study was through the stages of data coding, data presentation and data verification. The results of this study show that: there were 27 uploads for the period April – September 2022 which the researchers analyzed. It was found that there were 3 contents on gender, 10 content on reproductive health and HIV, 3 content on sexual rights and human rights, 4 content on violence, 1 content on diversity and 3 content on relationships. Researchers also consider that Instagram is quite effective as a medium in providing sexuality education, especially for teenagers who on average follow technological developments.